Biliary lipid composition in cholesterol microlithiasis. Issue 5 (1st May 2001) - Fracchia, M; Pellegrino, S; Secreto, P; Gallo, L; Masoero, G; Pera, A; Galatola, G
Abstract : BACKGROUND: Little information is available on the pathogenesis of cholesterol microlithiasis, and it is not clear if biliary lipid composition in these patients is similar to changes seen in cholesterol gall stone patients. AIMS: To measure biliary lipid composition in patients with cholesterol microlithiasis. PATIENTS: Eleven patients with cholesterol microlithiasis, 20 cholesterol gall stone patients, and 17 healthy controls. METHODS: Duodenal bile was collected in the fasting state during ceruletide infusion. Biliary cholesterol, phospholipids, and total bile acids were analysed by enzymatic assays, and conjugated bile acids by high pressure liquid chromatography. RESULTS: Patients with microlithiasis had a cholesterol saturation index significantly higher than controls (mean value 1.30 (95% confidence interval 1.05–1.54) v 0.90 (0.72–1.08)) but similar to gall stone patients (1.51 (1.40–1.63)). This was due to a significant decrease in per cent phospholipid (10.0% (7.1–12.8)) compared with controls (21.4% (18.1–24.6)) and gall stone patients (24.9% (20.5–29.3)). Per cent cholesterol was similar in patients with microlithiasis and controls (5.3% (4.5–6.1) and 5.6 % (4.3–6.8), respectively) but was significantly increased in gall stone patients (10.9% (9.3–12.4)). Bile acid composition in patients with microlithiasis was similar to controls whereas in gall stone patients deoxycholic acid was significantly increased: 27.3% (24.8–29.7) v 19.0% (15.7–22.2) in controls and 20.6% (14.9–26.2) in patients with microlithiasis. CONCLUSION: Patients with cholesterol microlithiasis have biliary cholesterol supersaturation, similarly to cholesterol gall stone patients. Whereas in the latter this is due to increased per cent cholesterol, in patients with microlithiasis this is caused by phospholipid deficiency, with normal per cent cholesterol and normal biliary bile acid composition.